Analisis Sedimentasi Pada Bendung Cadasgantung Desa Sindangsari Kecamatan Cigedug Kabupaten Garut - Depi Prayogi; Adi Susetyaningsih; Sulwan Permana (Jurnal Konstruksi, 2025)
Irrigation is a crucial component in the agricultural sector for enhancing productivity and ensuring food security. Adequate availability of irrigation water is essential for farmers to support crop cultivation activities. One of the most vital irrigation infrastructures is the weir, which functions to retain and raise the river water level so it can be diverted into irrigation channels.Cadasgantung Weir is located in Sindangsari Village, Garut Regency, West Java Province, at coordinates 07'18’04.1” S and 107'48’18.9” E. One of the main issues in the operation of weirs is sedimentation. Sediment accumulation in hydraulic structures can reduce storage capacity and affect the lifespan of the structure. This study aims to analyze the characteristics and quantity of sediment accumulated at Cadasgantung Weir. The analysis includes material type, particle size, sedimentation rate, and its impact on the weir’s functionality. The methods used involve numerical analysis using the HEC-RAS program and analytical calculations based on the Meyer-Peter Müller formula. The results show that the sediment at the weir is predominantly composed of medium-grained sand, with 60% of the particles having a diameter of 0.4641 mm. The sedimentation rate is highly influenced by water discharge, with a rate of 77.018 tons/day at base flow discharge, increasing to 607.736 tons/day at a 25-year return period (Q25). Meanwhile, at 50-year (Q50) and 100-year (Q100) return periods, the sedimentation rates are lower, recorded at 136.321 tons/day and 146.308 tons/day, respectively.Therefore, effective sediment management is necessary to maintain the optimal function of the weir.